인적자본과 혁신행동의 관계에서 조직몰입의 매개효과 -호텔기업을 중심으로 - 하용규; Ha, Yong-Kyu (한국콘텐츠학회 논문지, 10(6), 2010)
This study aimed to explore the relationships among human capitals, organizational commitments, innovative behaviors of employees in a deluxe hotel in Seoul. The results of this study are, human capitals have a direct impact on organizational commitments, and innovative behaviors. and organizational commitments directly influence to innovative behaviors.. And organizational commitments have a mediating effect partially between human capitals and innovative behaviors. These results suggest that the new direction of the importance of human resource managements on accumulating human capitals in organization and the importance of organizational commitments of employees on competing environments in the hotel industry for competitive advantage. 본 연구는 호텔기업의 인적자본이 조직몰입 및 혁신행동에 미치는 영향과 조직몰입이 인적자본과 혁신 행동의 관계에 미치는 매개효과를 밝혀내고자 서울지역에 소재한 특등호텔 종사원을 대상으로 실증분석을 시행하였다. 그 결과 인적자본이 조직몰입과 혁신행동에 영향력이 있고, 조직몰입이 혁신행동에 유의한 영향력이 있음을 밝혀냈다. 또한 조직몰입이 인적자본과 혁신행동의 관계에 부분적인 매개효과를 나타냄을 밝혀냈다. 이 결과는 호텔기업 인적자본의 중요성 및 종사원의 조직몰입이 경쟁환경에서 우위를 점하기 위한 중요한 역할을 한다는 새로운 방향을 시사하는 결과라고 할 수 있다.